2015
DOI: 10.1158/1078-0432.ccr-15-0586
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies for Taxane-Induced Peripheral Neuropathy in ECOG-5103 and ECOG-1199

Abstract: Purpose Taxane induced peripheral neuropathy (TIPN) is an important survivorship issue for many cancer patients. Currently, there are no clinically implemented biomarkers to predict which patients might be at increased risk for TIPN. We present a comprehensive approach to identification of genetic variants to predict TIPN. Experimental Design We performed a genome wide association study (GWAS) in 3431 patients from the phase III adjuvant breast cancer trial, ECOG-5103 to compare genotypes with TIPN. We perfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 29 publications
5
130
1
2
Order By: Relevance
“…The predictive strategies have predominantly focused on the search for hereditary biomarkers that could identify patients at increased risk of toxicity through candidate gene or genome-wide association studies (5,11,12). However, the findings from these studies done to date have identified nonoverlapping single or pathway biomarker associations that preclude immediate clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive strategies have predominantly focused on the search for hereditary biomarkers that could identify patients at increased risk of toxicity through candidate gene or genome-wide association studies (5,11,12). However, the findings from these studies done to date have identified nonoverlapping single or pathway biomarker associations that preclude immediate clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of patients with early-stage breast cancer did not show an association between self-reported black race and CIPN; however, a genome-wide association study of patients in the same study found an association between genetically determined African ancestry and taxane-induced CIPN. 7 Similarly, in an analysis from a SWOG adjuvant breast cancer trial, an African American-specific haplotype was associated with an almost threefold increase in risk of CIPN. 17 These studies did not have information on baseline diabetes.…”
mentioning
confidence: 97%
“…Previously, we reported that compared to all other races, AAs had higher risk of experiencing grade 2-4 TIPN; HR=2.1 (p=9.4 ×10 -15 ) and grade 3-4 TIPN; HR=2.7 (p=7.4 ×10 -13 ), respectively. 17 When assessed for impact of genetic ancestry on the risk of various definitions of hypertension in the bevacizumab containing arms (arms B and C), African ancestry was associated with significantly more grade 3-4 hypertension (OR=1.6; p=0.02), a trend toward more patients with one SBP measurement >160 mmHg (OR=1.4; p=0.07) or one SBP measurement >180 mmHg (OR=2.1; p=0.03); Figure 3. Finally, there was a trend for more AA patients that had CHF (OR=1.8; p=0.08); Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…15,17,18 In this study we have compared the likelihood of each of these clinically relevant toxicities between AAs and EAs. We report a numerically higher likelihood for each of these toxicities for AA's; with odds ratios ranging from 1.4-2.9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation